Myo-inositol improves developmental competence and reduces oxidative stress in porcine parthenogenetic embryos - Jawad, Ali; Oh, Dongjin; Choi, Hyerin; Kim, Mirae; Ham, Jaehyung; Oh, Byoung Chol; Lee, Joohyeong; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2024)
ObjectiveMyo-inositol (Myo-Ins), the most abundant form of inositol, is an antioxidant and plays a crucial role in the development and reproduction of mammals and humans. However, information elucidating the role of Myo-Ins in porcine embryonic development after parthenogenetic activation (PA) is still lacking. Therefore, we investigated the effect of Myo-Ins on porcine embryos and its underlying mechanisms.MethodsIn this study, various concentrations of Myo-Ins (0, 5, 10, and 20 mM) were added to the porcine zygotic medium (PZM3) during the in vitro culture (IVC) of porcine embryos. Several characteristics were evaluated, including cleavage rate, blastocyst formation rate, intracellular glutathione (GSH) and reactive oxygen species (ROS) levels in 4–5 cell stage embryos, total cell number, apoptotic rate in blastocysts, mitochondrial membrane potential (MMP), mitochondrial quantity, mitochondrial stress in the blastocysts, and gene expression for antioxidant and mitochondrial function markers. Additionally, the immunofluorescence of HO-1 was assessed.ResultsThe results showed that Myo-Ins at concentrations of 10 and 20 mM significantly increased the blastocyst formation rate compared to the control group. Embryos supplemented with 20 mM Myo-Ins exhibited higher GSH levels and lower ROS levels than those in the control group. Myo-Ins supplementation also decreased the rate of apoptosis and the apoptotic index in the treatment groups. Additionally, embryos supplemented with 20 mM Myo-Ins showed increased mitochondrial membrane potential (MMP), greater mitochondrial quantity, and reduced oxidative stress in the mitochondria. Interestingly, the expression levels of genes related to mitochondrial function and the nuclear erythroid factor 2-related factor (NRF2) pathway were elevated in the Myo-Ins treated groups. Furthermore, immunofluorescence results indicated that 20 mM Myo-Ins significantly increased HO-1 expression in blastocysts compared to the control group.ConclusionIn conclusion, 20 mM Myo-Ins supplementation enhanced blastocyst development and improved mitochondrial function by regulating apoptosis, reducing oxidative stress, and activating the NRF2 pathway.